Does Intention Really Lead to Actual Use of Technology? A Study of an E-learning System among University Students in Malaysia - Lo, May-Chiun; Ramayah, T.; Abang Azlan, Mohamad (Croatian Journal of Education, 2015)
This paper intends to investigate the long debated notion of whether intention really leads to actual behavior in the e-learning environment. A model based on the Technology Acceptance Model (TAM) was tested using data gathered through a structured questionnaire with participation of undergraduate students from a number of universities in Malaysia. Using the variance based structural equation modeling analysis of Partial Least Square (PLS) the model obtained a GoF value of 0.602 which exceeded the 0.36 cut-off value for large effect sizes of R2, thus providing adequate support to validate the PLS model globally. All the hypotheses developed were corroborated with strong support for the Intention related to the Actual use, thus confirming the validity of the TAM in e-learning and within a context of a developing country. Implications for developers and administrators are further elaborated.